High Altitude May Protect Against the Early Development of Irreversible Pulmonary Hypertension in Patients With Congenital Heart Disease - Inge vonAlvensleben; Brian B. Graham; Gustavo A. Balanza; Carlos Brockmann; Ericka C. Pérez; Ximena Y. Vicente; Carla Arteaga; Claudia Scherer; Franz P. Freudenthal; Rubin M. Tuder; Alexandra Heath (Pulmonary Circulation)
ABSTRACT Congenital heart disease (CHD) occurs at increased prevalence at high altitude, but there may be a paradoxical later onset of the development of Eisenmenger syndrome. We hypothesized that congenital heart disease patients at high altitude are protected from an early onset of irreversible pulmonary hypertension. We present a ospective observational case series study, supported by a PVRI grant, of patients in La Paz, Bolivia, located at 3600 m, who underwent surgery for CHD. 10 consecutive patients aged 5 to 29 years (mean 12) with left‐to‐right shunts and pulmonary hypertension underwent diagnostic catheterization to assess pulmonary pressure pre‐operatively and six to 9 months postoperatively, and had a lung biopsy performed at the time of the surgery. Control lung tissue was obtained from patients living at the same altitude who underwent pulmonary hydatid cyst resection. 10 CHD patients and 4 control patients were analyzed. Pre‐operatively, the patients had a significant response to hyperoxia with a fall in mean pulmonary pressure (mPAP) from 59.6 mmHg (SD 7.74) to 46.3 mmHg (SD 11.1); (p < 0.05). Postoperatively, the patients had an excellent response to surgery, with a mPAP of 26.4 mmHg (SD 6.42) (p < 0.05 vs. preoperative pressures). Analysis of the lung histology did not show evidence of pulmonary vascular remodeling in the CHD patients compared to the control patients. During the follow‐up in up to 11 years, pulmonary pressure assessed by echocardiography remained normal. In conclusion, chronic hypobaric hypoxemia at high altitude may delay the development of pulmonary vascular disease in CHD patients.